Evaluation of the water-equivalence of plastic materials in low- and high-energy clinical proton beams. (13th April 2017) - Lourenço, A; Shipley, D; Wellock, N; Thomas, R; Bouchard, H; Kacperek, A; Fracchiolla, F; Lorentini, S; Schwarz, M; MacDougall, N; Royle, G; Palmans, H
Abstract: The aim of this work was to evaluate the water-equivalence of new trial plastics designed specifically for light-ion beam dosimetry as well as commercially available plastics in clinical proton beams. The water-equivalence of materials was tested by computing a plastic-to-water conversion factor, H pl, w . Trial materials were characterized experimentally in 60 MeV and 226 MeV un-modulated proton beams and the results were compared with Monte Carlo simulations using the FLUKA code. For the high-energy beam, a comparison between the trial plastics and various commercial plastics was also performed using FLUKA and Geant4 Monte Carlo codes. Experimental information was obtained from laterally integrated depth-dose ionization chamber measurements in water, with and without plastic slabs with variable thicknesses in front of the water phantom. Fluence correction factors, k fl, between water and various materials were also derived using the Monte Carlo method. For the 60 MeV proton beam, H pl, w and k fl factors were within 1% from unity for all trial plastics. For the 226 MeV proton beam, experimental H pl, w values deviated from unity by a maximum of about 1% for the three trial plastics and experimental results showed no advantage regarding which of the plastics was the most equivalent to water. Different magnitudes of corrections were found between Geant4 and FLUKA for the various materials due mainly to the use of different nonelastic nuclear data. Nevertheless, for the 226 MeV proton beam, H pl, w correction factors were within 2% from unity for all the materials. Considering the results from the two Monte Carlo codes, PMMA and trial plastic #3 had the smallest H pl, w values, where maximum deviations from unity were 1%, however, PMMA range differed by 16% from that of water. Overall, k fl factors were deviating more from unity than H pl, w factors and could amount to a few percent for some materials.